Effect of cooking and in vitro digestion on the peptide profile of chicken breast muscle and antioxidant and alcohol dehydrogenase stabilization activity. (October 2020) - Xiao, Chuqiao; Toldrá, Fidel; Zhou, Feibai; Gallego, Marta; Zhao, Mouming; Mora, Leticia
Graphical abstract: Highlights: Cooking and digestion influence antioxidant and ADH stabilization activity of chicken peptides. Titin and collagen peptides were responsible for the main differences between samples. Cooking and digestion increase oxidized peptides and influence bioactivity. Chicken breast is a potential source of antioxidant and ADH stabilizing peptides. Abstract: The present study aimed to investigate the effect of cooking and simulated gastrointestinal digestion on the antioxidant and alcohol dehydrogenase (ADH) stabilization activity of peptides extracted from chicken breast muscle. Results showed that cooking would not affect peptide bioactivity, whereas further digestion using gastrointestinal enzymes could lead to significant changes, producing an increase in ORAC (112.5 to 682.0 uM TE/g) and ABTS radical scavenging activities (164.0 to 848.9 uM TE/g), whereas a decrease in DPPH radical scavenging (from 36.1% to 4.4%), ferric-reducing power (OD 700 from 0.50 to 0.15) and ADH stabilization activities (from 44.1% to 20.5%) was observed. The peptidomic analysis resulted in the identification and relative quantitation of 777 peptides from 76 different parent proteins and evidenced that peptides derived from titin and collagen were mainly responsible for the differences detected in the peptide profile. The decrease of DPPH radical scavenging, ferric reducing power, and ADH stabilization activity may result from the release of inactive peptides containing oxidized residues, mainly from collagen, leading to the loss of efficacy of active sequences. The results confirmed the importance of collagen derived peptides on the antioxidant and ADH stabilization activity observed in chicken breast as well as the negative impact of oxidation on the bioactivity of generated peptides after simulated gastrointestinal digestion. Nevertheless, further work would be needed to confirm the peptide sequences responsible for the observed bioactivity.